Allogeneic hematopoietic cell transplantation for lymphoma: baseline and posttransplant prognostic factors. Issue 8 (3rd August 2018) - Ko, Sun-Hye; Lee, Jung-Hee; Lee, Je-Hwan; Park, Han-Seung; Choi, Eun-Ji; Seol, Miee; Lee, Young-Shin; Kang, Young-Ah; Jeon, Mijin; Lee, Kyoo-Hyung
Abstract: The present study aimed to investigate baseline and posttransplant prognostic factors for allogeneic hematopoietic cell transplantation (HCT) in 61 lymphoma patients. The 5-year probabilities of overall survival (OS), non-relapse mortality (NRM), progression-free survival (PFS), and event-free survival (EFS) were 31.1%, 28.8%, 38.8%, and 23.2%, respectively. Multivariate analysis demonstrated that the International Prognostic Index risk at HCT was a significantly independent prognostic factor for OS, NRM, PFS, and EFS, and chemosensitivity was a prognostic factor for OS, NRM, and EFS. The occurrence of chronic graft-versus-host disease (GVHD) was significantly associated with higher OS, but it was not with PFS or EFS. Various parameters of immune reconstitution at 1 month after transplantation were associated with clinical outcomes in different ways. Our study results might be helpful in selecting appropriate patients or adopting effective posttransplant treatment strategies, eventually leading to an improvement in outcomes after allogeneic HCT for lymphoma.